[Ni3(iPr2Im)3(µ2‐CO)3(µ3‐CO)] – A CO‐Stabilized NHC Analogue of the Parent Neutral Nickel Chini‐Type Cluster. Issue 21 (23rd May 2019) - Berthel, Johannes H. J.; Kuntze‐Fechner, Maximilian W.; Radius, Udo
Abstract : The reactivity of nickel tetracarbonyl [Ni(CO)4 ] with the N ‐Heterocyclic Carbenes (NHCs) 1, 3‐diisopropylimidazolin‐2‐ylidene ( i Pr2 Im) and 1, 3‐di( iso propyl)‐4, 5‐di(methyl)imidazolin‐2‐ylidene ( i Pr2 Im Me ) is reported. The reaction of [Ni(CO)4 ] with two equiv. i Pr2 Im and i Pr2 Im Me and one equiv. i Pr2 Im Me leads to the formation of the complexes [Ni( i Pr2 Im)2 (CO)2 ] 2, [Ni( i Pr2 Im Me )2 (CO)2 ] 3, and [Ni( i Pr2 Im Me )(CO)3 ] 4 . The reaction of [Ni(CO)4 ] with one equiv. (or less) i Pr2 Im affords the triangular 44 VE (valence electron) cluster complex [Ni3 ( i Pr2 Im)3 ( µ 2 ‐CO)3 ( µ 3 ‐CO)] 1, a NHC‐stabilized analogue of the parent neutral nickel Chini cluster [Ni3 (CO)3 ( µ 2 ‐CO)3 ]. Abstract : The synthesis and characterization of complexes [Ni( i Pr2 Im)2 (CO)2 ], [Ni( i Pr2 Im Me )2 (CO)2 ], [Ni( i Pr2 Im Me )(CO)3 ], and of the triangular 44 VE Chini‐type cluster complex [Ni3 ( i Pr2 Im)3 ( µ 2 ‐CO)3 ( µ 3 ‐CO)] are presented.